Insights into Hierarchical Structure–Property–Application Relationships of Advanced Bacterial Cellulose Materials. (19th January 2023) - Wu, Zhuotong; Chen, Shiyan; Li, Jing; Wang, Baoxiu; Jin, Mengtian; Liang, Qianqian; Zhang, Dong; Han, Zhiliang; Deng, Lili; Qu, Xiangyang; Wang, Huaping
Abstract: Bacterial cellulose (BC) is an environmentally friendly biomaterial that is widely investigated because it possesses a unique hierarchical nanofiber network structure as well as extraordinary performance. In this review, the formation of the BC hierarchical nanofiber network structure from the perspective of biosynthesis is illustrated based on its basic chemical and crystal structure. Moreover, the design and processing of BC‐based advanced materials through biosynthesis, physical, and/or chemical modification are also reviewed. The intrinsic characteristics of BC, derived from its hierarchical structure, are analyzed to understand its structure–property–application relationships. The applications of advanced BC‐based materials are reviewed, such as high‐strength structural materials utilizing the properties of nanofibers, energy conversion and storage, bioelectronic interfaces, environmental remediation, and thermal management applications utilizing the ion transport properties and 3D network structures of these materials. In addition, the authors also offer their opinions and potential future research directions for sustainably developing BC‐based materials. Abstract : Bacterial cellulose (BC) is an environmentally friendly biomaterial that has been widely investigated. Based on its unique hierarchical nanofiber network structure and extraordinary performance, the structure–property–application relationships of BC are analyzed. The applications of advanced BC‐based materials in high‐strength structural materials, energy conversion and storage, bioelectronic interfaces, environmental remediation, and thermal management are reviewed.